Sociocultural influences on body image in female patients with eating disorders: an explanatory model - Pérez-Bustinzar, Ana Regina; Valdez, Mariana; Rojo Moreno, Luis; Radilla Vázquez , Claudia Cecilia; Barriguete Meléndez, Jorge Armando (Psychology, Society & Education, 2023)
Introduction: theories related to body image suggest that the influence of sociocultural patterns encourages women to internalize certain patterns and develop a high drive towards thinness. Objective: to analyze a model based on the Tripartite Influence Model that explains how social pressures contribute to greater body dissatisfaction that would lead to feelings of low self-esteem, fear of gaining weight, and a greater desire to lose weight in patients with eating disorders. Method: the sample consisted of 195 women with an age range of 12 to 30 years (M = 18.63, SD = 2.87) diagnosed with Anorexia Nervosa, Bulimia Nervosa, and Eating Disorder Not Otherwise Specified. The patients were interviewed for their diagnosis and two psychometric instruments were also applied. Subsequently, through a structural equation modeling analysis, a model was proposed for the patients. Results: the sociocultural factor that contributed the most to explain body dissatisfaction was the influence of the family. The model had a good fit. Discussion: the evidence obtained suggests that sociocultural factors, and in particular the influence exerted by the family, would contribute to the processes of body image formation in patients with eating disorders. The results of this study can be used by health professionals focused on patients with eating disorders in both clinical and research settings.